2015
DOI: 10.3390/pharmaceutics7030320
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a siRNA Carrier Modified with a pH-Sensitive Cationic Lipid and a Cyclic RGD Peptide for Efficiently Targeting Tumor Endothelial Cells

Abstract: In recent years, anti-angiogenic therapy has attracted much interest because it is a versatile approach to treating most types of tumors, and therefore would be expected to be applicable for various cancers. Severe adverse events in patients treated with currently available anti-angiogenic therapeutics have, however, been reported, and these are caused by their inhibitory effects in normal tissue. To achieve an efficient anti-angiogenic therapy with minimal toxicity, a drug delivery system (DDS) specific to tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…54 Therefore, cRGD cyclic peptides, that have the sequence: cyclo (Arg-Gly-Asp-D-Phe-Cys), were used to modify hybrid phospholipids membrane aer coating ADG cores to achieve long-circulation prole and tumor targeting. 55 First, the RGD specically acts on the surface of the tumor cells or the surface of the a v b 3 integrin receptor on the tumor vascular endothelial cells. 56 Then the cell surface specic proteolytic enzyme cleaves the cRGD peptide to form an activated CendR peptide which can specically recognizes and activates the neuropilin-1 receptor on the cell surface and can therefore achieve targeted delivery through the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…54 Therefore, cRGD cyclic peptides, that have the sequence: cyclo (Arg-Gly-Asp-D-Phe-Cys), were used to modify hybrid phospholipids membrane aer coating ADG cores to achieve long-circulation prole and tumor targeting. 55 First, the RGD specically acts on the surface of the tumor cells or the surface of the a v b 3 integrin receptor on the tumor vascular endothelial cells. 56 Then the cell surface specic proteolytic enzyme cleaves the cRGD peptide to form an activated CendR peptide which can specically recognizes and activates the neuropilin-1 receptor on the cell surface and can therefore achieve targeted delivery through the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…We previously examined the effect of a longer PEG-linker length (over 2,000) on in vivo knockdown efficiency. However, no drastic change was observed among PEG 2,000 , PEG 3,400 and PEG 5,000 linkers (Hada et al, 2015). It is generally known that long PEG chain hinders the cellular uptake and the endosomal escape of nanocarrier due to the ability to stabilize the membrane of liposomes, so called "PEG-dilemma" (Hatakeyama et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that the RGD-MEND had the ability to suppress mRNA and protein expression specifically in TECs (ED50: 0.75 mg siRNA/kg) [37,38].…”
Section: Introductionmentioning
confidence: 99%